Microbiological evaluation of Acacia angustissima as a protein supplement for sheep - Odenyo, A.A.; Osuji, P.O.; Karanfil, O.; Adinew, K. (Elsevier, 1997)
The effect of Acacia angustissima on rumen fermentation was evaluated. Acacia angustissima was fed to two groups of cannulated Ethiopian highland sheeOne group (three animals) was directly supplemented with 300 g per head day-1 of sun-dried A. angustissima. These animals died after 9 and 21 days and consumed only 75-100 g day-1 of the supplement at any time. The second group (three animals) was gradually adapted by offering incremental levels of 50, 75, 100, 150 and 200 g per head day-1 of A. angustissima for 21 days per level. The gradually adapted animals did not develop toxicity symptoms suggesting adaptation of microflora in the rumen or ability to modify the toxic principle in the plant. Transfer of rumen contents from the adapted animals to other unadapted sheep provided protection from A. angustissima toxicity when the animals were suddenly challenged with 200 g per head day-1 of A. angustissima toxicity when the transfer. Numbers of ciliate protozoa and fungal sporangia were estimated. The protozoal numbers fluctuated with the level of the supplement and numbers decreased in sheep consuming 100, 150 and 200 g of the supplement. The fungal sporangia numbers were inversely related to protozoal numbers. Effect on in sacco fibre (native hay) degradation was also investigated. There was no significant difference (P>0.05) in fibre degradation in sheep supplemented with A. angustissima compared with those fed maize stover alone. The effect of level of supplement was, however, significant (P<0.01). In vitro effect of A. angustissima on mixed ruminal bacteria was investigated using gas and volatile fatty acid (VFA) production as indices of fermentation. Gas and VFA production from A. angustissima were significantly (P<0.01) lower than those from Sesbania sesban (used as control) at 12 h. Acetone (70 percent) extracts of A. angustissima inhibited the growth of Ruminococcus albus 8, Ruminococcus flavefaciens FD-1, Prevotella ruminicola D31D and Streptococcus bovis JB1 while Selenomonas ruminantium D was not affected at the levels used. Bacterial colonies resistant to toxicity of A. angustissima were isolated.